Raising Hope. The complete third season [videorecording (DVD)]. - Leachman, Cloris; Dillahunt, Garret, 1964-; Plimpton, Martha, 1970-; Neff, Lucas, 1986-; Woodward, Shannon, 1984- (20th Century Fox Home Entertainment, 2013)
It takes a village, or as The Chance family proves, it takes one well-intentioned but slightly nutty family to raise Hope. Season three include the bumpy road to the alter for Sabrina and Jimmy, the casting of Hope on 'Yo Zappa Do' and the plot to break Maw Maw out of the nursing home, or should they? With relentless laughs and a stellar cast, Raising Hope charmingly reminds us that happiness is making the best of what we are given.